Juridical Analysis of the Serang Administrative Court Decision No. 24/G/2020/PTUN-SRG on the Building Permit Process for a Poultry Farm in Panyaungan Jaya Village According to Law No. 5 of 1986 on the Administrative Court - Heriansyah, Heriansyah; Fathullah, Fathullah; Kamseno, Sigit; Mabsuti, Mabsuti (SEAN Institute, 2025)
This research aims to analyze the judicial reasoning of the Serang State Administrative Court (PTUN Serang) Decision No. 24/G/2020/PTUN-SRG regarding a dispute over the issuance of a Building Permit (IMB) for a poultry farm in Panyaungan Jaya Village, Serang Regency. The main problem lies in the inconsistency between the local government’s administrative decision and statutory regulations, particularly in relation to the General Principles of Good Governance (AUPB). The study employs a normative juridical method with statutory, conceptual, and case approaches. Data were collected from primary, secondary, and tertiary legal materials, complemented by interviews to provide empirical validation. The results indicate that the PTUN Serang decision is consistent with Law No. 5 of 1986 on the State Administrative Court, Law No. 30 of 2014 on Government Administration, and Law No. 32 of 2009 on Environmental Protection and Management. The court found that the issuance of the IMB lacked legality and due diligence because it was not preceded by environmental assessments (UKL-UPL) and did not involve community participation. As a result, the administrative act was declared legally defective and annulled. Conceptually, the ruling reinforces the PTUN’s role as the guardian of the rule of law and a supervisory mechanism over administrative actions that may infringe upon citizens’ rights. Practically, this study underscores the importance of legality, transparency, and accountability in administrative decision-making, as well as the need for effective enforcement mechanisms to ensure compliance with PTUN judgments.